2018
DOI: 10.1016/j.marpetgeo.2018.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Age constraints on intra-formational unconformities in Upper Jurassic-Lower Cretaceous carbonates in northeast Turkey; geodynamic and hydrocarbon implications

Abstract: Upper Jurassic-lowermost Cretaceous carbonate build-ups are imaged on seismic data in the Black Sea. They form important, untested, hydrocarbon reservoirs that are the focus of active exploration. Outcrop analogues to these build-ups around the Black Sea contain a series of subaerial exposure surfaces. The hiatuses associated with a number of these subaerial exposure surfaces have been dated in a well exposed Callovian or Upper Oxfordian to Barremian shallow-water inner platform carbonate succession (the Berdi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 53 publications
4
27
0
1
Order By: Relevance
“…This age of rifting, based on fault study, is close to some ages proposed based on stratigraphic studies (e.g. Finetti et al, 1988;Görür, 1988;Görür et al, 1993;Okay et al, 1994;Robinson et al, 1995;Nikishin et al, 2008;Vincent et al, 2016;2018).…”
Section: -Conclusionsupporting
confidence: 88%
See 2 more Smart Citations
“…This age of rifting, based on fault study, is close to some ages proposed based on stratigraphic studies (e.g. Finetti et al, 1988;Görür, 1988;Görür et al, 1993;Okay et al, 1994;Robinson et al, 1995;Nikishin et al, 2008;Vincent et al, 2016;2018).…”
Section: -Conclusionsupporting
confidence: 88%
“…This angular unconformity indicates Late Albian tectonic uplift and erosion that results either from rift flank thermal uplift as suggested for a thick lithosphere (Robinson et al, 1995;Spadini et al, 1996;Cloetingh et al, 2003), or from continental collision, as suggested by Aptian-Albian metamorphic ages in the Central Pontides (Okay et al, 2006, Hippolyte et al, 2017. Note that in the Eastern Pontides, hiatuses of the latest Kimmeridgian to Berriasian and Hauterivian to Barremian were also interpreted as evidences of rift flank uplift during regional extension (Vincent et al, 2018).…”
Section: 3-age Of the Black Sea Riftingmentioning
confidence: 88%
See 1 more Smart Citation
“…These reefs are regarded as close analogues to the Late Jurassic reefs found in the Shatsky Ridge (Afanasenkov et al 2005;Guo et al 2011). The Ai-Petri Massif is a spectacular example of the Late Kimmeridgian-Tithonian reef complex Olszewska 2006, 2007) resembling the Štramberk-type reefs well known from the Pontides, Moesia, Southern Carpathian, Polish and Czech Outer Carpathian, Southern Crimea and the Northern Caucasus Mts (e.g., Matyszkiewicz and Słomka 2004;Bucur and Săsăran 2005;Ivanova et al 2008;Guo et al 2011;Piskunov et al 2012;Pleş et al 2013;Kaya and Altiner 2015;Kołodziej 2015;Strzeboński et al 2017;Hoffmann et al 2017;Vincent et al 2018). The main part of the Late Jurassic successions from the Crimean Mts.…”
Section: Location and Geological Settingmentioning
confidence: 99%
“…The Black Sea opened as an oceanic back‐arc basin during the Santonian, and led to the separation of the Pontides from Eurasia (e.g., Nikishin et al, ). The episodes of documented subduction were separated by periods of quiescence; most notably in the Late Jurassic–Early Cretaceous (157–130 Ma) when carbonates were deposited throughout the Black Sea region with no evidence of active subduction (e.g., Vincent et al, ). Oceanic subduction under the Pontides ended in the latest Cretaceous to Paleocene when the Pontides collided with the Anatolide‐Tauride Block leading to the north‐vergent deformation of the Pontide margin.…”
Section: Tectonic Setting and Stratigraphy Of The Ankara Regionmentioning
confidence: 99%